The Interrelation of Transparency, Public Participation, Accountability, and Policy Effectiveness: A Qualitative Approach to Good Governance Practices in Ambon City - Hadijah Madubun; Rina Nuraini Selly (Jurnal Mamangan, 2025)
This study explores the interrelationship between transparency, public participation, accountability, and policy effectiveness within the local governance context of Ambon City. Using a qualitative descriptive approach, data were collected through in-depth interviews, participant observation, and document analysis involving 15 key informants, including government officials, community leaders, civil society representatives, and academics. The study found that transparency serves as the foundation for effective governance by providing access to information, which enables citizen engagement and strengthens accountability mechanisms. Public participation, however, often remains formalistic, with limited integration of community input into decision-making processes. Accountability is primarily administrative and financial, with social accountability mechanisms underdeveloped. Policy effectiveness is closely linked to the integration of these governance principles, particularly in programs that combine interdepartmental coordination with participatory monitoring, such as Smart City initiatives and waste management reforms. The findings highlight a dynamic and reciprocal relationship among transparency, participation, and accountability, wherein weakness in one component affects the overall governance cycle. Challenges include limited digital literacy, bureaucratic resistance, and weak public oversight, while opportunities lie in digital governance platforms, youth-led civic groups, and academic collaborations. The study concludes that good governance in Ambon City is best operationalized as an evolving ecosystem of trust, collaboration, and adaptive accountability, rather than mere regulatory compliance. Recommendations include enhancing citizen-friendly transparency initiatives, fostering deliberative participation, and expanding mechanisms for public accountability. These insights provide guidance for local government reforms and serve as a reference for similar medium-sized cities in Indonesia